Visual Candi Jiwa Dalam Perspektif Practice-Based Research Sebagai Inspirasi Pembuatan Desain Headpiece - Dion Darsa Sabrian; Nadia Rachmaya Ningrum Budiono; Wening Gilang Nawangi; Puji Rahmah Shalih (UNIVERSITAS INDO GLOBAL MANDIRI, 2026)
This study explores how the aesthetic values of the Jiwa Temple Site in Karawang can be transformed into an artwear headpiece design. The research is motivated by the need for new approaches to preserving the cultural identity of the Jiwa Temple Site, which is currently facing physical deterioration, natural weathering, and damage caused by human activities due to its location in an open rice-field area. As an alternative form of cultural preservation, this study develops a headpiece inspired by the temple's architectural form and symbolic characteristics. The main objective of this research is to reinterpret the visual and structural elements of the Jiwa Temple Site into a contemporary headpiece design that offers both aesthetic originality and cultural meaning. To achieve this objective, the study adopts a Practice-Based Research approach, supported by descriptive analysis to examine the temple's visual characteristics and semiotic analysis to interpret the cultural meanings represented in its architectural elements. The results show that the transformation process successfully translates the visual grandeur of the Jiwa Temple Site into a lightweight wearable artwork without losing its aesthetic identity. The resulting headpiece not only contributes to the development of artwear design from both practical and theoretical perspectives but also functions as an alternative medium for introducing and promoting local cultural heritage, thereby encouraging greater public awareness of its preservation.